EMOTIONAL CULTURE AS AN INDICATOR PROFESSIONALISM OF THE MODERN TEACHER (Pedagogy of Higher and Secondary Education, 2022)
Emotional culture as index of professionalism of modern teachers”. In the article, the role of emotional culture is examined in becoming professionalism of modern teachers. On the basis of analysis of the results of pedagogical experiment the ways of forming of emotional culture among the students of pedagogical higher educational establishments are offered.